Analisis Kesalahan Siswa SMP dalam Menyelesaikan Soal Cerita Transformasi Geometri Berdasarkan Teori Newman - Reza Ahmadi; Gembong, Sardulo; Tanjung, Sri (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
This research aims to analyze the mistakes of class IX students of SMP Negeri 6 Madiun in solving geometric transformation story problems. The research method used was descriptive qualitative with research subjects being four students (one boy and three girls) chosen randomly from the class. The instruments used consisted of written tests and interview guidelines. The results of the analysis show that students face several main errors in the process of solving mathematics story problems. Identified errors included reading errors, where some students were unable to identify key information in the question; errors in understanding concepts, especially in applying the concept of geometric transformation correctly; difficulty in transforming story problems into appropriate mathematical models; errors in calculation process skills, where some students fail to carry out calculations correctly even though they use the right method; as well as errors in writing final answers, where some students did not include clear conclusions in their answers. The implication of these findings is the importance of improving student learning and coaching in critical aspects such as reading skills, understanding mathematical concepts, transformation abilities, calculation process skills, and answer writing strategies. This research contributes to the development of more effective mathematics curriculum and teaching methods at the junior high school level, with a focus on improving students' conceptual understanding and practical skills in solving mathematics problems in real contexts. It is hoped that the results of this research can become a basis for improvements in a more holistic and effective approach to mathematics learning in the future.